PENGARUH MERGER BANK SYARIAH INDONESIA DALAM PEREKONOMIAN MASYARAKAT INDONESIA - Hidayani (Program Studi Perbankan Syariah, 2021)
In economic development, especially in Islamic finance in Indonesia, it is still very high and has great potential because of the Indonesian population, capital market, sharia hospital, hotel, tourism, halal food, fashion, and much more. Especially in Islamic banking, as recently as February 2, 2021, Indonesia was mostly Muslim. The Islamic economic sector in Indonesia includes Islamic banking, non-bank finance already owns Bank Syariah Indonesia (BSI), the result of the merger of three state-owned banks (BUMN), especially in dealing with conventional banks. It is expected to be a bright prospect for the world of Islamic banking in Indonesia.. Observers assess that this target can only be achieved if the participating banks can consolidate well and transform digitally on a massive scale. The research method used in this paper is qualitative where the authors seek data through direct interviews with customers.. With the merger, it is hoped that it will open up many new opportunities for Indonesian Islamic Banks.. Because each of the merged Islamic banks already has qualified capabilities or different potentials in their fields so that it will strengthen BSI's position in the future.